Implementation of Islamic business ethics and its impacts on family business - Sampurno, Wahyu Mijil (Universitas Islam Indonesia, 2016)
This study is aimed to analyse the Islamic business ethics and how it affects the companies. The subject of the study is a home industry which process the milkfish in Pemalang, Central Java. The Islamic business ethics used are based on the five axioms, they are tawhid, balance, free desire, charity and responsibility. While the effects are measured by the six business progress parameters, they are marketing aspect, management aspect, human resources aspect, law aspect, social aspect, environment effect aspect and financial aspect. The data collection of the study is done by the qualitative descriptive approach. The result of the study shows that generally the company has applied the Islamic business ethics based on the referred five axioms. Besides, the Islamic business ethics application on the company also has effects on the six aspects of the company business progress.